Keabsahan Akad Jual Beli Menggunakan Bahasa yang Berbeda Perspektif Hukum Islam di Bangkalan - Dya Arini, Nuraziza (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2021)
Buying and selling is the most powerful activity in the business world. As long as it comes from buying and selling, it is strictly prohibited and has legal interference. Therefore, it is incumbent on muslims to know the things that determine the legitimacy of these trades. As in the shallows, banyal traders who were less able to speak Indonesian, and many of the foreigners who could not speak madura, so there was a different use of language between the traders and the buyers for the study's purpose to interpret: (1) language use in the buy and sell agreement in the bangkalan region: (2) an islamic law perspective on the validity of the buying and selling agreements in different languages. The method used in the study is a descriptive method using qualitative data analysis that describes the perspective of islamic law regarding the use of different merchant and customer languages. The data collection was used with observation and recording of the source of this research asa distinct form of language between the merchants and shoppers in the bangtal region. The results of this study are described as follows: 1). The activity of using language in the buy and sell agreement in the bangkalan region: 2) the perspective of islamic law regarding the legality of the buying and selling agreements in different languages.